INCREASE SOCIO-IDEOLOGICAL ACTIVITY IN THE ORGANIZATION OF EDUCATIONAL WORK IN THE HIGHER EDUCATION OF OUR COUNTRY - Xadjayev Olimxon Shavkatovich (Galaxy International Interdisciplinary Research Journal, 2023)
As you know, in pedagogical science, three major factors affecting personality maturation are studied in continuity and consistency. These are: heredity factor, social environment factor and upbringing factor. At this point, it will not be a mistake if it is said that the motive also has a role in acting as a factor. Social activity is a complex process and does not occur suddenly in a person. Studies conducted have shown that the formation of social activity in a student’s personality coincides with the period in which he chose this profession. The earlier the teacher realizes the responsibility and difficulties of his profession, especially its place on the path of the interest of the people and prosperity of the Motherland, the faster the buds of social activity are formed.